Народнорозмовна лексика як матеріал "Словаря української мови" Бориса Грінченка та перекладів Миколи Лукаша - Федунович-Швед, О.Т. (Лексикографічний бюлетень, 2014)
Inexhaustible source of Ukrainian’s national spoken language was for M. Lukash simultaneously as the source of translational inspiration and the treasure house of language’s instrumentals. Th e translator read and studied B. Grynchenko’s «Ukrainian language dictionary» carefully, thereby it became for him as the foundation of learning of national vocabulary and phraseology. Th e article deals with national spoken language vocabulary that refl ects simultaneously in B. Grynchenko’s «Ukrainian language dictionary» and in M. Lukash translations. Special att ention focused on using the vocabulary units, that have illustrated from Krolevechyn records, the place from which M. Lukash came.